Morocco - Poverty Report : Strengthening Policy by Identifying the Geographic Dimension of poverty - World Bank (Washington, DC, 2013)
The report provides detailed information on the geographical distribution of poverty and vulnerability throughout the country - i.e. regions, provinces and communes. The information presented is essential to understand poverty at the local level, and to address it with appropriate sectoral or cross-sectoral strategies. Further, when local poverty rates are analyzed alongside public expenditure data, an initial assessment for targeting performance of government social programs in rural and urban areas, is possible. The analysis finds that social programs generally are well targeted to the poor zones in rural areas, but not so in urban areas. The report also discusses the importance of identifying the distributional impacts of growth enhancing reforms, so that social protection policies for the poor and vulnerable can be designed to accompany the implementation of the reforms. The report examines in depth one important policy issue - de-protection of cereals -- and sheds light on the household impact of de-protection, with particular focus on the poor and vulnerable. By identifying which specific income groups and in which regions will be mostly hurt by the reforms in the short term, it will be possible to design appropriate social protection for vulnerable groups, and thereby support the agricultural reform process.